Partitioning a regional groundwater flow system into shallow local and deep regional flow compartments. Issue 4 (30th April 2013) - Goderniaux, Pascal; Davy, Philippe; Bresciani, Etienne; de, Jean‐Raynald; Le, Tanguy
Key Points This work studies the groundwater flow structure as a function of recharge in 3D A two‐compartment model quantifies local and regional transfers Partitioning of recharge and volumes associated to both compartments are studied